50 let Geografskega inštituta Antona Melika ZRC SAZU - Natek, Milan (Geografija Slovenije, 1999)
The book, published to celebrate the fiftieth anniversary of Anton Melik Geographical Institute, outlines the main features of the institute, such as the establishment and development as well as the main stages of the research work over the years. The institute, being part of the Scientific Research Centre of Slovenian Academy of Sciences and Arts since 1981, is comprised of five departments: the Department of Geoecology, the Department of Regional Geography, the Department of Natural Disasters, the Department of Geographical Information Systems and the Department of Thematic Cartography. Besides this it houses a library, geographical collections, a cartographic collection and the Commission for the Standardisation of Geographical Names appointed by the Government of the Republic of Slovenia.Rich additional material, mainly photos, that result from the research projects (the Triglav glacier and the glacier below Skuta, natural disasters and alpine farms) as well as from the preparatory work for numerous geographical publications about Slovenia and its landscapes, complements the text.